Does university performance matter for EU programmes in South East Europe : case study Horizon 2020 - Ajdarpašić, Suada (Array, 2019)
This paper examines the educational system in South East Europe (SEE) within the framework of opportunities coming from the European Union, particularly Horizon 2020, a recent EU innovation and research programme. The specific goal of this article is to measure the impact of the performance of universities in South East Europe and the likelihood of obtaining EU programmes, specifically Horizon 2020 projects. The additional aim is to investigate whether high-ranking universities are successful in obtaining Horizon 2020 projects and, more specifically, if university performance is a significant factor in the success rate in obtaining Horizon 2020 projects. In order to analyse this phenomenon empirically, we compare the main public universities of South East Europe and consider their overall performance in relation to EU programmes obtained. The final outcome of the paper is that there is a clear relationship between the university performance and obtaining Horizon 2020 projects. Therefore, the high performance of a university positively correlates with a high success rate in obtaining Horizon 2020 projects for most of the universities.